1993
DOI: 10.1097/00001888-199308000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Studentsʼ psychosocial characteristics as predictors of academic performance in medical school

Abstract: The "noncognitive," or psychosocial, measures increased the magnitude of the relationships between the predictive and criterion measures of the students' academic performances, beyond the magnitude attained when only the conventional admission measures were used. Therefore, psychosocial measures should be considered as significant and unique predictors of performance in medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
7

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 0 publications
1
50
0
7
Order By: Relevance
“…An assessment by psychosocial questionnaires has been reported to predict basic sciences grades, clinical sciences grades and clinical clerkships ratings (Hojat 1993). Personal statements, essays and autobiographical letters have been reported to predict performance in medical school (Eva et al 2004), a future choice of career in family medicine (Hull et al 1996) and ranking for admission for Internal Medicine residency and OSCE scores at the end of the pre-clinical studies (Peskun et al 2007).…”
Section: Selection Of Applicants For Medical School 511mentioning
confidence: 99%
“…An assessment by psychosocial questionnaires has been reported to predict basic sciences grades, clinical sciences grades and clinical clerkships ratings (Hojat 1993). Personal statements, essays and autobiographical letters have been reported to predict performance in medical school (Eva et al 2004), a future choice of career in family medicine (Hull et al 1996) and ranking for admission for Internal Medicine residency and OSCE scores at the end of the pre-clinical studies (Peskun et al 2007).…”
Section: Selection Of Applicants For Medical School 511mentioning
confidence: 99%
“…A depressão causa grande sofrimento psíquico e diminuição no rendimento acadêmico, com impacto na vida profissional futura dos estudantes de medicina (Hojat et al, 1993). No entanto, há necessidade de mais explorações para se avaliar o real impacto na vida acadêmica e futura do médico (Dyrbye, Thomas, & Shanafelt, 2006).…”
Section: Introductionunclassified
“…Some studies reported significant relationship between medical students' personality and academic performance (Leivens et al, 2002;Hoschl & Kozeny, 1997;Meredith et al, 1982), while others did not find such a link (Aldrich, 1987;Green et al, 1992). Yet, other studies indicate that personality attributes significantly predict academic success in medical school beyond measures of acquired knowledge (Hojat et al, 1993;1988). Similarly, higher ratings of postgraduate clinical competence, made by residency program directors, have been found to be associated with lower anxiety, emotionality, loneliness, positive perception of the mother, and to perception of relationships with peers .…”
Section: Introductionmentioning
confidence: 99%